Pengaruh Viral Marketing dan Live Streaming Terhadap Keputusan Pembelian Konsumen Pada Toko Nabila Fashion - Putri Nabila; Ismunandar Ismunandar; Ovriyadin Ovriyadin (Journal Economic Excellence Ibnu Sina, 2024)
Technological developments have changed consumer behavior in purchasing fashion products, especially through online platforms and social media. Viral marketing and live streaming are the main strategies in influencing purchasing decisions by reaching consumers widely and in real-time. This research aims to explore the influence of these two strategies on consumer purchasing decisions at the Nabila Fashion Store. This study identified several problems such as less interesting viral content, lack of product explanations from influencers, unstable networks during live streaming, promotions that are too long, and lack of consistency in promotions via social media. Based on this background, the research problem formulation includes the partial influence of viral marketing, the partial influence of live streaming, and the simultaneous influence of both on consumer purchasing decisions. The research results show that both viral marketing and live streaming have a significant influence on purchasing decisions. Viral marketing helps in disseminating product information quickly and effectively, while live streaming provides direct experiences to consumers, influencing purchasing decisions through real-time interactions and exclusive promotional offers. In conclusion, the implementation of viral marketing and live streaming can increase consumer purchasing decisions at the Nabila Fashion Store. Recommendations include improving the quality of viral content, improving network stability during live streaming, shortening the duration of promotions, and increasing consistency in promotions via social media to maximize influence on consumer purchasing decisions.